The Rise of Paratransit Digital Platforms in Large African Metropolises: Competitive Strategies between International and Local Platforms - (:unkn) unknown (My University, 2020)
Since the 2010s, large African metropolises have experienced unprecedented development of ICTs, of which paratransit digital platforms provide a striking illustration in the transport sector. In many of these metropolises local platforms (i.e., digital platforms for paratransit that are native of Africa) are competing fiercely with international platforms, although said competition has been little documented by academic literature so far. This paper has two main scientific purposes: partly filling the gap in academic literature on paratransit digital platforms in the African continent, and investigating the competitive dynamics between international and local platforms in the area. Based on a systematic census of, and extensive data collection on, paratransit digital platforms, the paper first provides an analysis of their geographical presence and deployment strategies across the continent. Then, the authors develop an exploratory analysis of the competition strategies (both price-based and innovation-based) of international and local paratransit digital platforms in 2018 and 2019 in nine metropolises: Accra (Ghana), Algiers (Algeria), Casablanca (Morocco), Cairo (Egypt), Dar Es Salaam (Tanzania), Johannesburg (South Africa), Kampala (Uganda), Lagos (Nigeria) and Nairobi (Kenya). The research reveals two different deployment patterns for international and local platforms across the continent, and an apparent convergence in prices among them when they provide similar services.
Keywords: African Research